THE EXISTENCE OF GOA GIRI PUTRI TEMPLE IN NUSA PENIDA KLUNGKUNG - Ni Putu Winanti; Ni Gusti Agung Ayu Nerawati (UHN I Gusti Bagus Sugriwa Denpasar, 2023)
The temple is an important part for Hindus to increase sraddha and devotion to Ida Sang Hyang Widhi Wasa. In this regard, Goa Giri Putri Temple in Karang Sari, Suwana Village, Nusa Penida District, Klungkung Regency, which is quite unique, needs to be studied about its structure, function, theological concepts and implications in a study from the perspective of Hindu theology. The issues raised are the reasons why Goa Giri Putri Temple still exists, the theological concept of Goa Giri Putri Temple and the implications of Goa Giri Putri Temple on people's lives in Nusa Penida Klungkung. The theory used is Structural Functionalism Theory. Data collection techniques through observation, interviews and literature study, and data analysis techniques with qualitative descriptive. Based on the analysis, it can be found that Goa Giri Putri Temple still exists because the Temple Management System was taken over by the Traditional Village, the Pelinggih Structure of Goa Giri Putri Temple is well managed, the opening of the Exit Way at the end of the Goa, and the establishment of the Pinandita Association. The Hindu theological concept of Goa Giri Putri Temple can be seen from the gods who are worshiped with various names, duties and functions, so that there is a divine concept of Saguna, Nirguna, Monotheism and Shivaistic. The implications of Goa Giri Putri Temple for the community can be seen from the Social Religious Society, Spiritual Tourism, Gender Equality, People's Economy, and Multiculturalism.